Results of clinic-morphological studies of sclera after surgical diathermy (experimental study) - I. V. Zapuskalov; O. I. Krivosheina; A. N. Dzyuman; Ya. A. Martusevich; O. B. Kochmala (Бюллетень сибирской медицины, 2009)
The inflammatory-reparative reactions of sclera after different injury were studied. In animals of the 1st group carried out conjunctivotomy and surgical diathermy. In animals of the 2nd group carried out conjunctivotomy. Biomicroscopy, histologic and morphometrical studies were carried out. The results demonstrate surgical diathermy of sclera leads to intensification of local inflammatory reaction and is a risk factor of excessive regeneration in glaucoma filtration surgery.